English as a Lingua Franca: Perceptions of Indonesian Non-Native English-Speaking Teachers (NNESTs) on English Pronunciation and Accents Identity - Ulfah Ridhwan Dirham (Scope : Journal of English Language Teaching, 2022)
The research examines how Indonesian non-native English-speaking teachers (NNESTs) perceive various English accents including Indonesian English speakers around them and their English accents as well in terms of native or non-native viewed from the lens of English as a Lingua Franca (ELF). In addition, the research also investigates how they perceive pronunciation identity reflected in their English accents. Qualitative methods were employed by using written online interviews. The participants consisted of five (5) Indonesian NNESTs whose English teaching experiences range from 10 to 32 years in universities in Jakarta. They were asked about their perception of accents and their colleagues’ accents and EFL practice in Indonesian English language teaching, especially in their environment where English is expected as the lingua franca of communication. The data were collected using written semi-structured interviews through email and speaking tests recorded through WhatsApp and analyzed using interpretivism adapted from the approach of phenomenology in teaching English. The result reveals their acceptance of being identified as belonging to a particular ethnicity or nationality due to salient characteristics of their accents as part of pronunciation identity. In addition, the result also shows acceptance of varied accents worldwide, yet they also unconsciously show their preference for American and British accents if they could choose to do so.